Pengaruh Sifat Materialisme terhadap Perilaku Impulsive Buying dan Kecenderungan Compulsive Buying Pada Remaja di Kota Mataram - Rini Anggriani; Abdurrahman Abdurrahman; Isra Dewi Kuntary Ibrahim; Raden Bagus Faizal (Universitas Bumigora, 2021)
The phenomenon of consumers’ behavior in shopping as the effect of the Covid-19 pandemic from offline to online indirectly has an impact on the prevalence of the increasing number of internet users in Indonesia. This study aims to identify whether there is a psychological influence of consumers such as the nature of materialism on impulsive buying and compulsive buying tendencies among adolescents in Mataram City. The sampling technique used was the purposive sampling method with a sample of 110. Data analysis used Structural Equation Modeling (SEM). The results showed that there was a positive and significant influence and relationship between the nature of materialism and impulsive buying. There is a positive and significant effect of materialism on compulsive buying tendencies. There is a positive and significant influence of impulsive buying on the tendency of compulsive buying in local teenagers in Mataram City.